Violencia y propiedad de la tierra en Colombia: el papel de las élites latifundistas (2020)
Land ownership is an issue of ongoing debate that is related to the causes of violence in Colombia, due to low access to land and lack of clarity on property rights. However, the following article explores the influence that latifundistas have had on public agrarian policy and how this has encouraged the accumulation of land, to the detriment of peasants. It is found that, based on a review of historical evidence in the existing literature, landowners and latifundistas have been in a privileged position to influence public policy, which has deepened violence in Colombia by reducing access to land for peasants and smallholders. The challenge in this situation is the implementation of the Havana peace accords on the agrarian question.